TALENT MANAGEMENT AND ORGANIZATIONAL PERFORMANCE IN OMAN GOVERNMENT HOSPITALS - Khalood Farzah; Nor Azilah Husin (International Journal of Accounting, Finance and Business, 2022)
Effective talent management requires an understanding of what core talent means, and how to leverage the talent in a manner that allows management to act decisively to drive competitive advantage as well as to secure the future success and sustainability of organisations. Research in healthcare setting in Oman reported non- punitive response to errors, inadequate staffing and hand offs and transition as areas of healthcare that require improvement in Oman. Given their engagement through talent management and great leadership is critical to improving morale and strengthening Oman healthcare professionals for optimum performance of healthcare system. Despite numerous studies on the topic so far little attention has been paid to talent management and the role of leadership in public hospitals setting. The aim of this research is to integrate elements from the individual, organisational and societal levels to gain a more comprehensive understanding of interactive relationship between talent management, healthcare professionals’ engagement and performance in Oman Government Hospitals. The study will contribute to the literature that exists on the concepts of this study, namely, talent management, employee engagement, leadership and hospital performance. The study seeks to benefit the hospital administrators particularly hospital management and government of Oman in general. A cross-sectional study among respondents from Sultan Qaboos Hospital Salalah and West Salalah Health Centre will be adequate as a good sample to conduct this study. A questionnaire containing four sections will be used to measure the variables in this study from healthcare professionals; points of view. A pre-test analysis will be carried out on 30 nurses in health centre in Salalah, not included in the sample of the study, to test the tool practicality and applicability. The data gathered will be analysed in AMOS software for structural equation modelling and the results will be disseminated.